TOWARDS COMMUNICATIVE CALL: IDEAS AND STRATEGIES FOR ITS PRACTICAL IMPLEMENTATION - Syariful Muttaqin (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2010)
This article presents some practical applications of computer in English language teaching and learning. As computer now is getting more accessible, it should be well utilized for enhancing students’ English skills. In addition, a lot of computer language laboratories have been set up in some schools. However, some of the facilities are useless because less preparation, low usability of the facility, and lack of maintenance so that the sustainability of the computer program at schools is very weak. This article explores what computer can do to help students learn English better and what teachers, students, and administrator have to do in order to achieve the English teaching and learning objectives.